Simultaneous Saccharification and Fermentation of Wheat Starch for Bioethanol Production - Vesna Vučurović; Aleksandra Katanski; Damjan Vučurović; Bojana Bajić; Siniša Dodić (Fermentation, 2025)
Bioethanol is a renewable, environmentally-friendly biofuel conventionally produced through the alcoholic fermentation of sugary or starch-rich substrates by microorganisms, commonly Yeast Saccharomyces cerevisiae. Intermediates of industrial wheat flour wet milling processing to starch, such as A-starch and B-starch milk, are cost-effective, abundant, and non-seasonal feedstocks for bioethanol production. This study evaluates the bioethanol production from wheat A-starch and B-starch milk and mixtures of these two substrates in different ratios (1:3, 1:1, and 3:1) using two cold hydrolysis procedures at 65 °C: (i) simultaneous liquefaction and saccharification (SLS) followed by fermentation, and (ii) liquefaction by alpha-amylase followed by simultaneous saccharification and fermentation (SSF). The results demonstrated that SSF and SLS are equally efficient procedures for reaching a high ethanol yield of 53 g per 100 g of starch and 93% of starch conversion to ethanol for all investigated substrates. Lower levels of non-starch components in A-starch milk, which typically contribute to volatile by-product formation, allowed clear distillate profiles in terms of and lower content of aldehydes, methanol, and volatile acidity, enhancing ethanol distillate purity compared to B-starch milk. Mixing high-quality A-starch milk with low-cost B-starch milk enables higher ethanol yield, improved distillate quality, and energy savings for efficient industrial-scale applications.